Interpreting the seventh century BC : tradition and innovation - Charalambidou, Xenia,; Morgan, Catherine, 1961- (Archaeopress Publishing Ltd, 2017)
This text has its origin in a conference held at the British School at Athens in 2011 which aimed to explore the range of new archaeological information now available for the seventh century in Greek lands.